Public actors in international investment law - Titi, Catharine, 1979- (Springer, 2021)
Traditional studies on actors in international investment law have tended to concentrate on arbitrators, claimant investors and respondent states. Yet this focus on the "principal" players in investment dispute settlement has allowed a number of other seminal actors to be neglected. This book seeks to redress this imbalance by turning the spotlight on the latter. From the investor's home state to domestic courts, from sub-national governments to international organisations, and from political risk insurance agencies to legal defence teams in national ministries, the book critically reviews these overlooked public actors in international investment law
Keywords: Investments, Foreign (International law); Investments -- Government policy.; Investissements étrangers (Droit international); Investissements -- Politique gouvernementale.; Investments -- Government policy